PENGEMBANGAN NOVEL : IT’S WRONG BUT I STILL WANT IT - Ajni Pratistha, Jenia Puspita; Windrawanto, Yustinus; Maria Agustin, Adhi Krisna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Friendship is currently done online through dating apps. The average user of dating apps is a teenager and is often known as Friend's With Benefit (FWB). Teenagers know Friend's With Benefit (FWB) through digital novels (wattpad). This study is a research on the development of novels as educational media and uses the Research and Development (R&D) method from Borg and Gall modified by Sugiyono (2008:275) which consists of seven stages. The data analysis technique uses a 4-point Likert Scale instrument. Expert testing uses 3 expert BK teachers to test the feasibility of the novel used. The results of the novel development are that teenagers can make decisions not to do FWB.